Solomon Islands Selected Issues (IMF Staff Country Reports, 2011)
This paper analyzes Solomon Islands' ongoing reforms concerning of the mineral taxation regime and the fiscal impact of mineral resources. The analysis shows that mineral revenue could be substantial, provided that mineral prices remain strong in the medium term. Enforcing the tax agreement with, a Gold Ridge company, and implementing the new resource taxation regime are critical to ensure that the forthcoming mineral wealth spills over to the rest of the economy. Solomon Islands should adopt new fiscal rules and fiscal responsibility provisions to manage large but volatile resource revenue